Analysis of Efficient Drug Supply Control at Muhammadiyah Siti Aminah Bumiayu Hospital Using the MMSL Method (Minimum-Maximum Stock Level) Period March – May 2023 - Sofia, Anna; Peranginangin, Jason Merari; Herdwiani, Wiwin (PT FORMOSA CENDEKIA GLOBAL, 2024)
Medicine supplies that are too large or small will make hospitals sick loss. These losses can be in the form of drug supply costs enlarges and becomes disturbed smooth running of health services in hospitals. Objective study This For know influence method MMSL to supply drug in a way efficient in Installation Pharmacy RSU Muhammadiyah Siti Aminah Bumiayu. This research design uses quasi-experimental without control, by applying the method studied, namely minimum-maximum stock levels. Sampling using technique which can be obtained from Retrospective data for October 2022 – December 2022 and method application prospectively, namely March 2023 - May 2023 and carry out strategies repair use method Hanlon. All data drug results analysis A B C became the sample for this research. Analysis of inventory value data was carried out, stock value out, dea d stock and ITOR before and after application of the method using test statistics Wilcoxon Signed Rank Test. The inventory value before applying the MMSL method was IDR 289,756,421, and after applying control using the MMSL method it was IDR 184,725,126 , with a value of p=0.002<0.05. The implementation of drug control using the MMSL method shows that there is an influence on the value of drug supplies in the pharmaceutical installation of RSU Muhammadiyah Siti Aminah Bumiayu.